Selection criteria for ecosystem condition indicators. (December 2021) - Czúcz, Bálint; Keith, Heather; Maes, Joachim; Driver, Amanda; Jackson, Bethanna; Nicholson, Emily; Kiss, Márton; Obst, Carl
Highlights: We propose an indicator development framework based on a systematic review, which: Consists of 12 well-justified criteria linked to the steps in an expert process. Distinguishes ecosystem characteristics and their indicators. Is applicable in many fields of ecological/environmental/sustainability indicators. Finally we identify two critical knowledge gaps for SEEA applications. Abstract: The UN System of Environmental-Economic Accounting Ecosystem Accounting (SEEA EA) aims at regular and standardised stocktaking of the extent of ecosystems, their condition, and the services they provide to society. Recording the condition of ecosystems is one of the most complex pieces in this exercise and needs to be supported by consistent guidelines. SEEA EA defines the condition of an ecosystem as its overall quality, measured in terms of quantitative metrics describing its abiotic and biotic characteristics. One of the key challenges lies in identifying the most appropriate metrics for each ecosystem type that capture these essential characteristics. The objective of this paper is to create a well-defined framework for transparent and operative development of ecosystem condition indicators, which can be used in ecosystem accounting and ecosystem assessment studies. Starting from the SEEA EA documentation and a small targeted systematic review, we identified 12 key criteria, which we grouped according to their roles during the indicator development process. Five conceptual criteria (intrinsic relevance, instrumental relevance, sensitivity, directional meaning, and framework conformity) outline the priorities for identifying relevant characteristics of the ecosystems. Five practical criteria (validity, reliability, availability, simplicity, and compatibility) provide guidance on identifying concrete quantitative metrics for the selected characteristics. Finally, two ensemble criteria (comprehensiveness, and parsimony) ensure the completeness and complementarity of the final set of metrics. To tackle the climate and biodiversity crises, the condition of ecosystems needs to be better recognized in national economic planning. The proposed framework supports the selection of a concise set of salient and credible ecosystem condition indicators through a transparent, repeatable and scientific process. This can make the compilation of ecosystem condition accounts more accessible and more standardised on a global level, which is a key prerequisite for the success of SEEA EA. Additionally, the framework presented in this paper may be useful in other contexts where ecological, environmental, or sustainability indicators need to be identified.